Immunological impact of graphene oxide sheets in the abdominal cavity is governed by surface reactivity - Rodrigues, Artur Filipe (Arch Toxicol, 2018)
Graphene oxide (GO) is an oxidised form of graphene that has attracted commercial interest in multiple applications, including inks, printed electronics and spray coatings, which all raise health concerns due to potential creation of inhalable aerosols. Although a number of studies have discussed the toxicity of GO sheets, the in vivo impact of their lateral dimensions is still not clear. Here, we compared the effects of large GO sheets (l-GO, 1–20 µm) with those of small GO sheets (s-GO, < 1 µm) in terms of mesothelial damage and peritoneal inflammation, after intraperitoneal (i.p.) injection in mice. To benchmark the outcomes, long and rigid multi-walled carbon nanotubes (MWCNTs) that were shown to be associated with asbestos-like pathogenicity on the mesothelium were also tested. Our aim was to assess whether lateral dimensions can be a predictor of inflammogenicity for GO sheets in a similar fashion as length is for MWCNTs. While long MWCNTs dispersed in 0.5% BSA induced a granulomatous response on the diaphragmatic mesothelium and immune cell recruitment to the peritoneal cavity, GO sheets dispersed under similar conditions did not cause any response, regardless of their lateral dimensions. We further interrogated whether tuning the surface reactivity of GO by testing different dispersions (5% dextrose instead of 0.5% BSA) may change the biological outcome. Although the change of dispersion did not alter the impact of GO on the mesothelium (i.e. no granuloma), we observed that, when dispersed in protein-free 5% dextrose solution, s-GO elicited a greater recruitment of monocytic cells to the peritoneal cavity than l-GO, or when dispersed in protein-containing solution. Such recruitment coincided with the greater ability of s-GO to interact in vivo with peritoneal macrophages and was associated with a greater surface reactivity in comparison to l-GO. In conclusion, large dimension was not a determining factor of the immunological impact of GO sheets after i.p. administration. For an equal dose, GO sheets with lateral dimensions similar to the length of long MWCNTs were less pathogenic than the MWCNTs. On the other hand, surface reactivity and the ability of some smaller GO sheets to interact more readily with immune cells seem to be key parameters that can be tuned to improve the safety profile of GO. In particular, the choice of dispersion modality, which affected these two parameters, was found to be of crucial importance in the assessment of GO impact in this model. Overall, these findings are essential for a better understanding of the parameters governing GO toxicity and inflammation, and the rational design of safe GO-based formulations for various applications, including biomedicine. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00204-018-2303-z) contains supplementary material, which is available to authorized users.